The Holy Spirit and Christian Origins: Essays in Honor of James D. G. Dunn. Edited by Graham Stanton, Bruce W. Longenecker, and Stephen C. Barton. Pp. xxii + 382. Grand Rapids, MI: William B. Eerdmans, 2004. isbn 0 8028 2822 1. £29.95/50 - Isaacs, Marie E. (The journal of theological studies, 2006)
This Festschrift to honour Jimmy Dunn on the occasion of his 65th birthday consists of 27 essays written by his fellow academics and former students. From the viewpoint of any reviewer that is large enough, but nothing compared with the number of books and articles (listed on pp. 360–75) of the honorand, which would delight the heart of any contemporary Head of Department having to take part in the Research Assessment Exercise! But Jimmy is more than prolific—he is also insightful and inspirational, as is evidenced in this volume., Given, as the editors point out (p. xx1, n. 16), that no fewer than 25 of Professor Dunn's publications have the word ‘spirit’ in the title, it is wholly appropriate that the topic of the Holy Spirit should be the focus of this collection.